The Wilson & Co. Internationally Famous Six-Horse Clydesdale Team- San Diego, Calif. 1935 (The General Printing Co.)
Horse Royalty thrills San Diego Visitors - the Internationally famouse $100,000 Six-Horse Clydesdale Team, owned by Wilson & Co., Chicago and Los Angeles meat packers, is one of the wonders to be seen at San Diego this summer during the California International Exposition. Don't fail to come to San Diego this summer